EXAMINATION IN AUDITING. - Meigs, Walter B. (The Accounting Review, 1962)
Abstract The article reports on the auditing section of the May 1962 Uniform C.P.A. examination, which has been conducted on May 17, 1962 from 8:30 to 12:00 noon and included two groups of questions as follows, one of the problem given is, "Your client is a small college in a small town. The college has recently elected as treasurer the president of the local bank in which the college keeps its cash funds. The bank is also the custodian of the college's endowment fund securities. Furthermore, certain short-term securities are held at the bank in a safe deposit box to which the president has access. Confirmation requests to the bank in the past have been signed by the former college treasurer and the bank's replies have been signed by the bank president." The problem has been answered briefly as, "the dual role played by the bank president who is now also treasurer of the client organization signifies the absence of normal internal controls over cash and securities. When internal controls are weak or absent, the auditor should extend and intensify the audit procedures bearing on the areas affected. In this case the auditor should arrange if possible for a college official other than the treasurer to sign the confirmation requests."